Garis Panduan Pemakaian Pakar Pengubatan Islam sebagai Suatu Keterangan Pendapat Pakar bagi Kes Jenayah Sihir - Muna bin Hamzan (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2022)
This study aims to guide the Shariah judiciary, especially the Prosecution Department and the judges, in determining Islamic medical experts as an expert opinion to be adopted in the trial for cases of magic crimes in Shariah courts. These Guidelines will also be the basis of reference and guidance to the state Islamic religious department (JAIN) and government agencies such as the Malaysian Islamic Development Department (JAKIM) related to certified Islamic medical experts. This study will discuss the conditions Ruqyah Syar'iyyah in Islamic medicine, the pillars Ruqyah Syar'iyyah in Islamic medicine, ethics of Islamic medicine practitioners, the conditions of Islamic medical practitioners in brief. In addition, this study also highlights the principles of Islamic treatment and etiquette of Islamic treatment practices. The methodology used in this study is a library study that is a list of documents such as books and articles. It is hoped that these guidelines can also provide understanding and explanation to Muslims in this country on thae conditions and ethics of Islamic medicine. In addition, it aims to identify true practitioners of Islamic medicine and coincide with the standards of Islamic requirements in the hope that the Muslim community will seek and receives treatment services from real practitioners of Islamic medicine. This step must be played collectively by all authoritative parties to introduce the true practice of Islamic medicine and comply with the principles of faith and Islamic law.